Pengaruh Disiplin, Motivasi, Budaya Organisasi terhadap Kinerja Karyawan Pabrik PT. Mitra Kerinci - Indria Ukrita; Giva Nivatul Husna; Roni Afrizal (Agriekstensia : Jurnal Penelitian Terapan Bidang Pertanian, 2024)
The company is inseparable from the intervention and contribution of human resources. The existence of human resources plays an important role in achieving company goals and can be started from employee performance. The company's main goal is to increase the quantity and quality of production so that the company continues to grow. In addition, the company must also be prepared to face the development of the industrial world where the emergence of similar companies results in competition. This type of quantitative data with respondents, namely permanent employees of the PT Mitra Kerinci factory totaling 32 people, the sampling technique is a census sample. Test (R2) the effect of independent variables on the dependent variable is 67.6% and 32.4% is influenced by other independent variables. Simultaneous test, F-count>from F-table 22,542>2,950 significance value 0.000 <0.05 discipline, motivation, organizational culture simultaneously affect performance. The t-test, discipline has no effect on performance because r-count>from r-table, significance 0.595, motivation and organizational culture affect employee performance because r-count>from r-table, significance 0.004 and 0.002. The implication of this research is an effort to improve employee performance for future company development.